An Optimality-Based Spatial Explicit Ecohydrological Model at Watershed Scale: Model Description and Test in a Semiarid Grassland Ecosystem - Chen, Lajiao; Hu, Zhidan; Du, Xiaoping; Khan, Mohd Yawar Ali; Li, Xiaojun; Wen, Jie (Frontiers in Environmental Science, 2022)
Optimality principles have been applied in ecohydrological modeling to derive optimal vegetation properties and describe co-evolution states of vegetation and water cycle. Unfortunately, most existing optimality-based models only consider vertical vegetation-soil-water interactions on plot scale, without considering the lateral hydrological processes. This work aims to extend the field-scale Vegetation Optimality Model (VOM) to the watershed scale. Lateral flow is incorporated to VOM through a hierarchical strategy, establishing the Distributed Vegetation Optimality Model (DisVOM). The model is tested with long-tem flux measurements in the Walnut Gulch watershed, a United States Agricultural Research Service (US-ARS) experimental watershed in southern Arizona. The results indicate the model performance is acceptable for most of years, especially for the growing season. The seasonal dynamic of ET, soil water, and GPP demonstrate good consistency with observations. The model provides reasonable spatial distribution of ET and GPP, suggesting the model can discriminate the effect of lateral flow on water redistribution, and consequently on root water uptake, as well as carbon assimilation. The model could be a useful tool assessing the impact of climate change and human activities on vegetation and water cycle.